ON THE EXAMINATION OF BALINESE CULTURES UPON ANIMAL AND PLANT LEXICONS IN BALINESE SONGS: AN ECO-LINGUISTICS STUDY - Widiatmika, Putu Wahyu; Bagus Made Ari Segara, Ida; Netra, I Made (International Journal of Humanity Studies (IJHS), 2023)
This study aims to know the relation of Balinese cultures with the animal and plant lexicons in Balinese songs from the perspective of eco-linguistics. The data from this study were collected from YouTube. Listening and documentation methods along with transcription techniques were applied to collect the data. The animal and plant lexicons found were subsequently analyzed using the method of descriptive-qualitative with the help of Bang and Døør’s theory of dialectical eco-linguistics and the eco-linguistics parameters from Fill and Muhlhausler. The result of this study shows that the animal and plant lexicons used resulted from the co-existence of Balinese people and other species in their environment. The lexicons are inserted into the songs through the concept of metaphor. The co-existence makes Balinese people able to give meanings towards the animal and plant in the song based on their cultures and beliefs.